Structural variation in the glycogen synthase kinase 3β and brain‐derived neurotrophic factor genes in Japanese patients with bipolar disorders. Issue 1 (26th November 2019) - Suga, Yosuke; Yoshimoto, Keiichiro; Numata, Shusuke; Shimodera, Shinji; Takamura, Shogo; Kamimura, Naoto; Sawada, Ken; Kazui, Hiromitsu; Ohmori, Tetsuro; Morinobu, Shigeru
Abstract: Background: Lithium is the first‐line drug for the treatment of bipolar disorders (BDs); however, not all patients responded. Glycogen synthase kinase (GSK) 3β and brain‐derived neurotrophic factor (BDNF) play a role in the therapeutic action of lithium. Since structural variations were reported in these genes, it is possible that these genomic variations may be involved in the therapeutic responses to lithium. Method: Fifty patients with BDs and 50 healthy subjects (mean age 55.0 ± 15.0 years; M/F 19/31) participated. We examined structural variation of the GSK3β and BDNF genes by real‐time PCR. We examined the influence of structural variation of these genes on the therapeutic responses to lithium and the occurrence of antidepressant‐emergent affective switch (AEAS). The efficacy of lithium was assessed using the Alda scale, and AEAS was evaluated using Young Mania Rating Scale. Results: Although we examined structural variations within intron II and VII of the GSK3 ® gene and from the end of exon IV to intron IV and within exon IX of the BDNF gene, no structural variation was found in BDs. Whereas 5 of 50 patients exhibited three copies of the genomic region within exon IV of the BDNF gene, all healthy subjects had two copies. No difference in the therapeutic efficacy of lithium was found between patients with three and two copies. No difference in the occurrence of AEAS was found between the two groups. Conclusion: The amplification of the BDNF gene influenced neither the therapeutic responses to lithium nor the occurrence of AEAS. Abstract : Five of 50 patients with bipolar disorders exhibited three copies of the genomic region within exon IV of the BDNF gene. But, 50 healthy subjects had two copies. This amplification did not affect the therapeutic responses to lithium.